A Computed Tomographic (CT) and Pathological Study of Equine Cheek Teeth Infundibulae Extracted From Asymptomatic Horses. Part 1: Prevalence, Type and Location of Infundibular Lesions on CT Imaging - Horbal, Apryle; Smith, Sionagh; Dixon, Padraic M. (Frontiers in Veterinary Science, 2019)
Background: Equine maxillary cheek teeth infundibulae are frequently affected by developmental and acquired disorders, but the computed tomographic (CT) imaging features of normal and abnormal infundibulae remain incompletely understood. Objective: To examine infundibulae with various grades of occlusal caries and control teeth by standard (spiral) CT in order to assess the prevalence, type and location of subocclusal infundibular lesions present. Study design: Ex vivo original study. Methods: 100 maxillary cheek teeth, including 82 with, and 18 without infundibular occlusal caries, were extracted from horses of different ages and imaged by spiral CT; 8 teeth were also imaged by MicroCT. Images were later assessed by Osirix® and the prevalence, characteristics and sites of infundibular lesions were assessed. Results: Teeth with shorter infundibulae (i.e. Triadan 09 position and older teeth) were more likely to have occlusal caries, as were the rostral infundibulae. Subocclusal infundibular lesions, including cemental hypoplasia and caries, were present in 72% of infundibulae without occlusal caries. CT imaging confirmed two main patterns of developmental cemental hypoplasia, i.e. apical cemental hypoplasia involving the full width of the infundibulum and central linear hypoplasia involving the central aspect of the infundibulum over most of its length, and combinations of these types. These developmental lesions could later be affected by (acquired) infundibular caries. Some “normal-sized” (i.e. circa 1mm diameter) occlusal central vascular channels expanded subocclusally to the dimensions of central linear defects. Main Limitations: No clinical histories or accurate ages were available for these teeth. Conclusions: Hypoplastic cemental lesions, including at central linear and apical sites, are common even in clinically normal maxillary cheek teeth and caries can occur when these lesions contact the occlusal surface. Central linear defects are not always clearly distinguishable from “normal” central vascular channels.